PENGARUH STRATEGI BELAJAR DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS X PELAJARAN AKUNTANSI SMK PGRI WONOASRI TAHUN AJARAN 2011/2012 - Ryfandi Andy Prasetya; Isti Apriliyanti; Henik Puspita Sari (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study aimed to analyze The Influence of Learning Strategies and Parental Concern Either Jointly or Independently to Class X Student Achievement Accounting Lessons SMK PGRI Wonoasri. The analysis method used multiple linear regression and hypothesis testing processed using SPSS. The results showed that the learning strategy has a positive and significant impact on achievement for students in learning achievement is affected by the use of learning strategies. Parental attention has a positive and significant impact on learning achievement because in learning achievement is also influenced by parental concern. Learning strategies and attention parents together has a positive and significant impact on academic achievement.